(untitled) (International journal of artificial intelligence, 2025)
This article provides a comprehensive overview of metaphor and metonymy in modern English. It explores their fundamental characteristics, cognitive functions, and roles in everyday language and literature. Additionally, the paper highlights how metaphor and metonymy influence communication, thought processes, and linguistic creativity.